Spectrophotometric determination of betaxolol in pure form and pharmaceuticals - Zhuk, Y. N.; Vasyuk, S. O.; Васюк, Світлана Олександрівна; Жук, Юлія Миколаївна (My University, 2016)
A new spectrophotometric method for the quantitative determination of betaxolol in pharmaceutical formulations, such as tablets, has been developed. This method is based on the formation of yellow complex as a result of the reaction between betaxolol and bromocresol green (3',3'',5',5''-tetrabromo-m-cresolsulfophthalein) with maximum absorption at 408 nm in acetone. The proposed method is valid according to the validation requirements of Ukrainian Pharmacopeia. According to the experimental data, the technique can be correctly reproduced and it is suitable for routine quality control.
Keywords: betaxolol; spectrophotometric determination; bromocresol green